CUSTOMARY APPROACH AND RULE OF LAW BY PANGLIMA LAOT IN RESOLVING FISHERMEN'S DISPUTE IN ACEH - Muhammad Nasir; Hasan Basri; Ferdy Saputra (Kanun Jurnal Ilmu Hukum, 2022)
This research aims to examine the effectiveness of Panglima Laot's institution authority in the maritim area to resolve sea disputes and to find an ideal dispute resolution model to be used. This research uses qualitative method by sociological juridical approach in the form of descriptive analytical. The Panglima laot's authority in an effort to assist the government in resolving maritime disputes is a formal authority granted by a law which is attributively regulated in Article 28 of Qanun Aceh Number 10 of 2008 concerning Customary Institutions. However, when dealing with certain cases between fishermen where the regulation is not very clear in the Qanun, Panglima Laot seeks to resolve cases by using traditional approaches, religious values, propriety, a sense of justice and human conscience. Therefore, Panglima Laot needs detailed and written instructions for carrying out tasks in the form of Government Regulations or Qanuns. Including dealing with refugees who come from abroad.